2017
DOI: 10.1039/c7ra10553c
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling vaginal microbial genetic diversity and abundance between Holstein and Fleckvieh cattle

Abstract: Characterization of bovine vaginal microbial genetic diversity can lead to better understanding of cattle physiology, which is of economic interest in improving cattle reproduction health. However, there is limited knowledge on the factors affecting the microbial community harbored in the vaginal tract. The aim of the current study is to evaluate and compare the microbial genetic diversity and abundance between the Holstein and Fleckvieh cattle using metagenomic approach. The main bacterial phyla found were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The different sections of the reproductive tract have distinct microbial populations; however, they can still influence each other. The vaginal niche is mainly comprised of the phyla Firmicutes, Bacteroidetes, and Proteobacteria [ 18 , 209 ]. A study of Bos Indicus breeds found the most abundant bacterial genera in the vagina were Aeribacillus , Bacillus , Clostridium , Bacteroides , and Ruminococcus [ 210 ].…”
Section: Microbiome-gut-organ Axesmentioning
confidence: 99%
“…The different sections of the reproductive tract have distinct microbial populations; however, they can still influence each other. The vaginal niche is mainly comprised of the phyla Firmicutes, Bacteroidetes, and Proteobacteria [ 18 , 209 ]. A study of Bos Indicus breeds found the most abundant bacterial genera in the vagina were Aeribacillus , Bacillus , Clostridium , Bacteroides , and Ruminococcus [ 210 ].…”
Section: Microbiome-gut-organ Axesmentioning
confidence: 99%
“…However, with the advent of advanced technologies such as metagenomics, similar groups of bacteria have been revealed in the Nellore, Holstein, and Fleckvieh cattle. Such bacteria at the phylum level specifically comprised Firmicutes, Bacteroidetes, and Proteobacteria [22,29] as depicted in Figure 2, and that constitute about 30-40% of the total bacteria present in the vaginal niche [30]. Recent studies by Giannattasio-Ferraz et al [31] have also revealed a substantial similarity existing between the vaginal microbiota of Nellore cattle and Gyr (which is also another essential breed) and the main bacterial species described were mainly Aeribacillus, Bacillus, Clostridium, Bacteroides, and Ruminococcus.…”
Section: Vaginal Microfloramentioning
confidence: 99%
“…A total of ten bacterial phyla were detected, including Firmicutes (47.5–53.5%) and Bacteroidetes (28.4–31.7%), which accounted for 79.2–82.3% of the total bacteria. Bacteroidetes is the dominant bacterial phylum in the rumen followed by Firmicutes and Proteobacteria [ 31 , 32 ]. However, the relative abundance of Firmicutes increases when the concentrate feed rate increases [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%